Competitive pricing on online markets: a literature review - Torsten J. Gerpott; Jan Berends (Journal of Revenue and Pricing Management, 2022)
Past reviews of studies concerning competitive pricing strategies lack a unifying approach to interdisciplinarily structure research across economics, marketing management, and operations. This academic void is especially unfortunate for online markets as they show much higher competitive dynamics compared to their offline counterparts. We review 132 articles on competitive posted goods pricing on either e-tail markets or markets in general. Our main contributions are (1) to develop an interdisciplinary framework structuring scholarly work on competitive pricing models and (2) to analyze in how far research on offline markets applies to online retail markets.
Keywords: 330; Competition; Competitive pricing; Dynamic pricing; e-commerce; e-tail; Online markets